A CRITICAL DISCOURSE ANALYSIS OF QUR’ANIC EXEGESIS: BHINNEKA TUNGGAL IKA (UNITY IN DIVERSITY) - Nasirin Nasirin; Teguh Arafah Julianto; Muhammad Hidayat; Ulyan Nasri (Tanzil: Jurnal Studi Al-Quran, 2025)
The interpretation of Bhinneka Tunggal Ika (Unity in Diversity) has long been invoked in Indonesia’s religious, national, and cultural discourse. While normatively understood as a call for tolerance and harmony, it has rarely been examined critically through the lenses of Qur’anic exegesis and discourse analysis. This article investigates how the discourse of Bhinneka Tunggal Ika is constructed and deployed within religious texts and broader social narratives, highlighting its implications for power and ideology. Using Critical Discourse Analysis, the study explores how narratives of unity often function less as inclusive engagements with diversity and more as instruments for legitimizing the dominance of majority groups or state authorities. Such interpretations tend to suppress alternative perspectives, particularly those voiced by marginalized communities. The findings indicate that the discourse of Bhinneka Tunggal Ika in tafsir is not neutral or universal but shaped by hegemonic interests and institutional frameworks that privilege uniformity over plurality. The study argues that religious interpretation must move toward a more critical and inclusive hermeneutics—one that not only affirms common values but also recognizes difference as an epistemic and spiritual resource. The broader implication is the necessity of opening tafsir studies to interdisciplinary approaches and dialogical engagement. By doing so, religious discourse can become more just, reflective, and liberating, contributing to a pluralistic public sphere that genuinely honors Indonesia’s foundational principle of Bhinneka Tunggal Ika.